DEVELOPMENT OF ENVIRONMENTAL PHYSICS TEACHING MATERIALS BASED ON GENERIC SCIENCE SKILLS IN THE FORM OF MODULES IN THE FORM OF A POCKET BOOK VIEWED FROM STUDENT LEARNING INTEREST - Nuraini Fatmi; Izkar Hadiya (Universitas Negeri Medan, 2020)
The study aims to determine the quality of the Environmental Physics pocket book based on generic science skills developed in terms of students' interest in learning before and after learning with a pocket book. The pocket book was developed through research and development (R & D.) abbreviated R&D. The research subjects were A2 class students of the Physics Education Study Program class of 2016. The research design to look at the effect of learning with a pocket book on learning interest was by one group pretest posttest. In addition to seeing the effect of learning with a pocket book on student learning interest, the developed pocket book also reviews students' responses to the pocket book during the development process. The research data in the form of students' interest scores were calculated by their N gain values, tested for normality and homogeneity and statistically tested by the t-sample statistical test. Student response data is calculated by the average percentage of positive responses and negative responses. The development of a pocket book has gone through a review process by two media experts and one material expert that has produced the result that a pocket book is suitable for use. The influence of pocket books on students' interest in learning that is pocket books can increase student interest in learning with an average N-Gain of 55% while the statistical t test conducted shows that the developed pocket books are able to significantly increase student learning interest.